The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ecc.13372
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐pocket spending of deceased cancer patients in five European countries and Israel

Abstract: Objective: Cancer imposes a substantial economic burden on society, health and social care systems, patients and their families. This study aims to examine the out-ofpocket spending of cancer patients in their last year of life, in six countries with health insurance system hat have a defined benefits package. Methods: Data from SHARE and SHARE End-of-Life surveys among people aged +50 were analysed. Family members of deceased persons were interviewed in order to learn about the circumstances of their relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Previous literature suggests that long-term BC survivors are less affected by OOP payments than patients in the initial treatment phase due to the lower need for healthcare services [ 30 , 36 , 39 , 40 ]. As for the extent of OOP payments, our results are similar to those of other studies that found OOP payments to be more common for direct medical costs (outpatient care in particular) and largest amounts to correspond to direct non-medical costs (domestic help and nursing staff) [ 39 , 69 , 70 ]. Furthermore, our results also suggest that OOP payments for long-term BC survivors in Germany rarely reach the catastrophic threshold (i.e., exceeding 15% of the annual household income) [ 71 – 73 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous literature suggests that long-term BC survivors are less affected by OOP payments than patients in the initial treatment phase due to the lower need for healthcare services [ 30 , 36 , 39 , 40 ]. As for the extent of OOP payments, our results are similar to those of other studies that found OOP payments to be more common for direct medical costs (outpatient care in particular) and largest amounts to correspond to direct non-medical costs (domestic help and nursing staff) [ 39 , 69 , 70 ]. Furthermore, our results also suggest that OOP payments for long-term BC survivors in Germany rarely reach the catastrophic threshold (i.e., exceeding 15% of the annual household income) [ 71 – 73 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study also found that predictors of reporting the highest amount of OOP expenses include age at time of diagnosis (65–79), education (10–11 years), (early) retirement, stage of diagnosis (stage III), time from diagnosis (more than 10 years), comorbidities (at least 1), and the use of rehabilitation services. Prior studies have also identified older and more educated BC patients to encounter higher OOP payments [ 17 , 24 , 59 , 60 , 67 , 70 , 74 , 82 84 ]. Pisu et al [ 85 ] and Newton, Johnson [ 68 ] also found OOP payments are the highest among survivors in (early) retirement, for whom a disability status is common and therefore make a higher use of healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…The two main determinants of OOP expenditure at the end of life of persons who succumbed to cancer and of their families were medications and private caregivers. The finding that a large share of people in Israel spent out of pocket for medications is consistent with findings from Europe and the United States that trace the main OOP expenditure for people with cancer to medications not included in public coverage, whereas spending for nursing is smaller in most countries 26 . It was found in this study, however, that the average outlay for a private caregiver is the highest among the expenditure items even though the standard deviation of OOP spending, especially on medications, is very wide, possibly attesting to large differences in expenditure.…”
Section: Discussionsupporting
confidence: 85%
“…Cancer is one of the costliest illnesses that a person can encounter [ 29 ] and the costs of its treatment are rising more briskly than in many other areas of healthcare [ 28 ]. Although cancer-related healthcare costs vary widely among countries [ 5 , 11 , 18 , 25 ], including countries that have universal healthcare systems, statutory health insurance, and/or strong health-technology assessment processes, supplemental out‐of‐pocket (OOP) expenses for cancer patients are common [ 26 ]. Health-insurance systems and insurers are increasingly passing costs of care onto patients by raising deductibles, introducing copayments, and taking out coinsurance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer care imposes a substantial economic burden not only on society and healthcare systems but also on patients and their families and relatives [ 6 , 7 ]. Although there are major differences in healthcare costs for cancer among countries [ 8 , 9 , 10 , 11 ], additional patient out-of-pocket expenses are prevalent even in countries with universal healthcare systems or health insurance for all [ 12 , 13 , 14 ]. Health-insurance systems and health insurers are increasingly shifting costs of care to patients by raising deductibles and imposing copayments [ 15 ].…”
Section: Introductionmentioning
confidence: 99%